The Rule of Organic Fertilizer on Fertilizer Efficiency and Requirement Rate for Vegetable Crop on Inceptisols Ciherang, Bogor - Ladiyani Retno Widowati (UNIVERSITY OF LAMPUNG, 2009)
Utilization of organic fertilizer is an alternative to increase soil health and supply a small amount of plant nutrient. Meanwhile agricultural soil in Indonesia commonly have low organic carbon content (<2%) therefore application of organic fertilizer is recommended. Based on that, the aim of the research is to measure the effectiveness of organic fertilizer on caisim (Brassica chinensis L.) growth, to measure the release of N-NO3- and N-NH4+, to determine the recommendation of organic fertilizer for caisim on Incentisols Ciherang, Bogor. The research had been conducted at Research and Soil Testing Laboratory and green house of Soil Research Institute, Laladon – Bogor on April to July 2008 using soil sample of Inceptisols Ciherang, Bogor. The treatments were: Control (No fert.), NPK, rates of NPK + 500 kg organic fertilizer, 500 kg and 1000 kg organic fertilizer (No NPK), NPK+250 and 750 kg organic fertilizer. The five replications research had been conducted with Completely Randomized Design. The result indicated thats: (1) NPK fertilizer increased with addition of organic fertilizer approved by the evidence of increasing of plant high 2-10%, leaves number 1-2%, and crop production 16-36%. The relative agronomic effectiveness (RAE) of treatment NPK+various rate of organic fertilizer were higher than NPK alone with value of 136-181%. (2) The release of NH4+-N and NO3–N from anorganic fertilizer (NPK treatment) in four weeks incubation period showed balance proportion with N rate. Nitrogen released from organic fertilizer in the same incubation period are 5.39 mg NH4+-N kg-1 and 12.39 mg NO3- -N kg-1. (3) The best organic fertilizer rate based on fertilizer curve for Inceptisols Cicadas-Bogor having low C and N-organic is 560 kg organic fertilizer + NPK (300 kg Urea ha-1; 50 kg SP-36 ha-1; 50 kg KCl ha-1) produce caisim 134 g bag-1.